The impact of cultural factors on consumer behavior: a holistic model for adaptive marketing approaches - Rachwal-Mueller, А.; Fedotova, I.; Рахвал-Мюллер, А.; Федотова, І. В. (Харківський національний автомобільно-дорожній університет, 2024)
The influence of cultural factors on consumer behavior is profound and encompasses a myriad of dimensions, ranging from fundamental cultural constructs, such as Hofstede's model, to specific components including language, religion, and material culture. In the face of globalization, which often promotes the homogenization of consumer preferences, cultural diversity remains a critical determinant in shaping brand perceptions and influencing purchasing decisions. This study delineates eight categories of cultural factors, encompassing values and beliefs, religious and moral principles, language and communication styles, material culture, aesthetics, education and knowledge systems, social institutions and organizations, as well as the dynamic interplay between globalization and local culture. These factors are systematically categorized into internal and external characteristics, underscoring the complex and multifaceted nature of cultural influences on the decision-making process. The research findings underscore the necessity for marketing strategies that are attuned to these cultural distinctions, thereby enhancing brand relevance across diverse markets. A nuanced understanding of these variances enables marketers to craft tailored approaches that resonate with consumers' cultural contexts, thereby optimizing engagement. To encapsulate the insights derived from this investigation, a theoretical framework illustrating the interrelations among the identified cultural factors influencing consumer behavior has been constructed. This comprehensive model offers a holistic perspective on how culture shapes consumer behavior, accentuating the intricate interconnections among various cultural elements. The findings indicate that marketing strategies must be inherently sensitive to cultural differences to effectively enhance brand relevance across multifarious markets. The insights garnered from this study contribute to the theoretical discourse on cultural influences in consumer behavior and pave the way for future research initiatives. An in-depth understanding of the dynamics of cultural diversity empowers organizations to formulate adaptive strategies that align with the expectations of diverse consumer segments. This strategic alignment not only fosters the development of more impactful marketing campaigns but also enhances brand loyalty and drives sales within the global marketplace.
Вплив культурних факторів на поведінку споживачів: холістична модель адаптивних маркетингових підходів
Keywords: consumer behavior; cultural factors; Hofstede's cultural dimensions; global perspective; cultural values; language; attitudes; cross-cultural marketing; globalization; поведінка споживачів; культурні фактори; культурні виміри Хофстеде; глобальна перспектива; культурні цінності; мова; переконання; кроскультурний маркетинг; глобалізація; 658.8:316.72; 10.30977/ЕТК.2225-2304.2024.44.165